Evaluation of the temperature and humidity index to support the implementation of a rearing system for ruminants in the Western Amazon - Silva, Welligton Conceição da; Printes, Oscar Vitor Nina; Lima, Dagmar Oliveira; Silva, Éder Bruno Rebelo da; dos Santos, Maria Roseane Pereira; Camargo Júnior, Raimundo Nonato Colares; Barbosa, Antônio Vinicius Corrêa; Silva, Jamile Andréa Rodrigues da; Silva, André Guimarães Maciel e; Silva, Lilian Kátia Ximenes; Araújo, Cláudio Vieira de; Britto, Elton Nunes; et al. (Frontiers in Veterinary Science, 2023)
The good productive and reproductive performance of the animals depends on multiple factors, including favorable climatic conditions, which are responsible for causing changes in the physiological and behavioral responses. Thus, the objective of this study was to evaluate the temperature and humidity index (THI) to support the implementation of a rearing system in ruminants in the Western Amazon, Brazil. Monthly temperature and relative humidity data were obtained from the Database for Teaching and Research (BDMEP) for the capitals Manaus (Amazonas), Boa Vista (Roraima), and Rio Branco (Acre), considering a historical series of 27 years (1993 to 2020), referring from January to December. In the capital Boa Vista, the months of January, February, May, June, and July showed an indication of mild stress and the months of March, April, August, September, October, November, and December had moderate stress. In Rio Branco, all months of the year presented the average THI in mild stress with variations of lower THI (73) and higher THI (77). In the capital Manaus, the months from January to July signaled mild stress, but from August to November, there was moderate stress, and in December, there was mild stress. It is possible to observe significant climatic variations during the months as well as the years of study, with the animals under thermal stress with THI > 72 or in a warning signal, with a gradual increase in temperature and humidity indices over the last 10 years. The importance of the breeding system and the consideration of environmental factors, such as the THI, are fundamental for the wellbeing and performance of cattle raised in the field. Our results support the adoption of heat stress mitigation strategies for ruminants in Western Amazon.